Quality of Liquid Waste at the General Hospital in Makassar - Bintang, Andi; Syafri, Muhammad; Rante, Anshar; Marpaung, Mauritz Pandapotan; Fitrah, Fitrah; Putri, Safridha Kemala; Yusrianto, Yusrianto (International Journal of Health Sciences, 2023)
Hospital waste is all waste produced by hospital activities and other supporting activities. Considering the impacts that may arise, good management efforts are needed including tools and facilities, finances and organizational procedures that are determined with the aim of obtaining hospital conditions that meet environmental health requirements. The research used was observational with a descriptive approach, namely to determine the quality of liquid waste in hospitals in Makassar. This research was conducted from 20 to 27 June 2021 at the Hospital in Makassar. The population is liquid waste in hospitals in Makassar in 2021. The sample in this study is hospital effluent waste in Makassar in 2021. Waste water that is not handled properly will result in negative impacts, especially for health, so it needs good management so that when it is disposed of in A certain area does not cause pollution which is supported by the wastewater treatment plant (IPAL) owned by the hospital itself. It was concluded that the DO levels in the liquid waste produced were at a vulnerable level. The BOD level in liquid waste in the morning is at a moderate level and in the afternoon it is at a heavy level. COD levels in Makassar liquid waste in the morning are at moderate levels and in the afternoon at heavy levels. TSS levels in liquid waste in the morning are at moderate levels and in the afternoon they are at heavy levels. The pH level in liquid waste meets the requirements. TEMPERATURE levels in liquid waste meet the requirements.